2019
DOI: 10.2175/106143017x15131012187980
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability metrics for assessing water resource recovery facilities of the future

Abstract: The recovery of water, energy, and nutrients from water resource recovery facilities (WRRFs) is needed to address major global challenges, such as increasing water demand and decreasing availability of non-renewable resources. To meet these challenges, innovative technological developments must lead to increased adoption of water and resource recovery processes, while addressing stakeholder needs (e.g., innovators, practioners, regulators). A testbed network of over 90 partner facilities within the U.S. and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 13 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…In recent years, the European Commission adopted an ambitious Circular Economy Package to promote the reuse, recycling, and recovery of wastes [26]. The reuse of biosolids on land application enhanced the recovery of resources (e.g., nutrients [27,28]) and, therefore allows changing the classic view of WWTP in a more sustainable water resources recovery facility (WRRF) [16,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the European Commission adopted an ambitious Circular Economy Package to promote the reuse, recycling, and recovery of wastes [26]. The reuse of biosolids on land application enhanced the recovery of resources (e.g., nutrients [27,28]) and, therefore allows changing the classic view of WWTP in a more sustainable water resources recovery facility (WRRF) [16,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The urban WWTPs can be an important part of circular sustainability thanks to integration with the concept of reuse of biosolids (BS), namely treated biological SS (Neczaj and Grosser, 2018). In this context, WWTPs can be reoriented to function as water resource recovery facilities (WRRFs) (Cornejo et al, 2019;Zhao et al, 2019). In fact, traditional WWTPs are focused on the goals of human health and environmental protection; in the WRRFs the goal of resource recovery, through subsequently BS reuse, is added (Cornejo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, WWTPs can be reoriented to function as water resource recovery facilities (WRRFs) (Cornejo et al, 2019;Zhao et al, 2019). In fact, traditional WWTPs are focused on the goals of human health and environmental protection; in the WRRFs the goal of resource recovery, through subsequently BS reuse, is added (Cornejo et al, 2019). BS, once considered a waste product by the industry, are now becoming increasingly recognised as a multifunctional resource with growing opportunities for marketable use (Short et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 14 , 27 , 28 Standardized P reporting is required to compare performance across different technologies and wastewater streams to accelerate technology adoption, yet a critical gap exists due to lack of a common set of metrics. 29 This knowledge gap in reporting metrics for P and its different chemical species is also highlighted in a recent systematic review of nutrient removal and recovery technologies by Kogler et al 30 In reviewing 292 articles across 46 sources, Kogler et al 30 found that removal efficiency and achievable effluent concentrations for P removal and recovery technologies are generally underreported, with only 16% of the articles reviewed giving adequate quantitative information for meaningful interpretation of technology performance.…”
Section: Introductionmentioning
confidence: 99%